1995
DOI: 10.1111/j.1753-6405.1995.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of educational visiting to improve benzodiazepine prescribing in general practice

Abstract: A randomised controlled trial studied the effect of an educational visit on benzodiazepine prescribing. An approximately representative sample of 286 general practitioners was allocated to an intervention or a control group. Rates of benzodiazepine prescriptions were derived from two comprehensive self-report surveys seven months apart. Two months after the first survey the intervention group received an educational visit and supporting material from a doctor or pharmacist, ostensibly unconnected with the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…When compared to control, 50% of the educational interventions targeted at GPs had significant decreased benzodiazepine use and 17% (1 study, [29]) which did not reduce overall use of benzodiazepines did significantly decrease the number of new patients being prescribed benzodiazepines.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to control, 50% of the educational interventions targeted at GPs had significant decreased benzodiazepine use and 17% (1 study, [29]) which did not reduce overall use of benzodiazepines did significantly decrease the number of new patients being prescribed benzodiazepines.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were excluded for the following reasons: intervention targeted at pharmacists, study protocol without results or incomplete methods description, or observational study design without a control group. The systematic review includes 15 studies: 11 RCTs and 4 observational studies [7,[19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Study Selectionmentioning
confidence: 99%
“…De Burgh et al evaluated the effect of AD on reducing benzodiazepines (BDZ) prescriptions for insomnia and anxiety [22] by comparing the rate of BDZ prescriptions per 100 patient encounters with diagnoses of anxiety or insomnia. The overall rate of BDZ prescriptions decreased by 23.7% between pre and post-intervention surveys (p < 0.001) in the entire study sample, but no statistically significant differences were observed between AD and controls (p = 0.2) in overall BDZ prescription rates or in prescription of BDZ for either anxiety or insomnia.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…For example, the state of New York implemented a triplicate prescription monitoring program that resulted in a decline in prescribing of BZDs by half [39]. Studies have evaluated educational visits to doctors to discuss alternative treatments for sleep disorders [40], and electronic medical record systems have implemented alerts and reminders to encourage prescription of safer medication alternatives [41]. Educational materials targeted at patients have also provided information on proper sleep hygiene [42].…”
Section: Discussionmentioning
confidence: 99%